Realistic Quasi‐Biennial Oscillation Variability in Historical and Decadal Hindcast Simulations Using CMIP6 Forcing. Issue 23 (3rd December 2019) - Pohlmann, Holger; Müller, Wolfgang A.; Bittner, Matthias; Hettrich, Sebastian; Modali, Kameswarrao; Pankatz, Klaus; Marotzke, Jochem
Abstract: We analyze the quasi‐biennial oscillation (QBO) variability of historical and decadal hindcast simulations of the MiKlip (Mittelfristige Klimavorhersagen) decadal prediction system using the higher resolved version of the Max Planck Institute Earth System Model. We find a realistic variability of the QBO in historical simulations when changing from the Coupled Model Intercomparison Project Phase 5 (CMIP5) to the Coupled Model Intercomparison Project Phase 6 (CMIP6) external forcing. This agreement between the simulated and the observed QBO is improved by the initialization of decadal hindcast simulations with CMIP6 forcing in the first three lead years. In the decadal hindcast simulations, the agreement is similar to a persistence forecast in the first five lead years and higher than the persistence forecast in the later lead years. We find a strong relation between the QBO and the ozone variability in the stratosphere and conclude that the change of the ozone data from CMIP5 to CMIP6 leads to the improved QBO variability and prediction skill in our simulations. Plain Language Summary: The quasi‐biennial oscillation (QBO) is a climate mode in the stratosphere with the feature of reversing wind directions above the equator roughly every second year (period of 28 months). The QBO variability has worldwide implications for other climate modes like the strength of the polar vortex that influences Europe via the North Atlantic Oscillation. Previous historical simulations with our climate model show that with a high vertical resolution, the model is able to produce a QBO variability, however, with an unrealistic phase. These historical simulations need external forcing like greenhouse gases and ozone concentrations. We show that in our simulations, the QBO variability becomes realistic when we use the updated external forcing data from Coupled Model Intercomparison Project Phase 6 (CMIP6) instead of those from CMIP5. Moreover, we find evidence that the variability of the stratospheric ozone data leads to the realistic QBO variability in our climate simulations. This has implications for decadal climate predictions since—for a good climate prediction—the stratospheric ozone variability must be projected into the future. Key Points: The QBO becomes realistic in historical and decadal hindcast simulations when the external forcing data are changed from CMIP5 to CMIP6 In the first three lead years, the forecast skill of the QBO is increased after the initialization of the decadal hindcasts with observations Evidence is found that the update of the ozone data in CMIP6 leads to the realistic QBO variability